Development of a Laser Test Range for the Italian Air Force: Airborne Laser Systems Performance Prediction, Safety Analysis, Flight Testing and Operational Training - Sabatini, Roberto (Department of Aerospace, Power and Sensors, 2008)
This thesis describes the research work performed for designing, developing and testing a new laser test and training range for the Italian Air Force. This includes the design of new range instrumentation and facilities, development of innovative methods for military systems performance prediction/evaluation and determination of eye-safety requirements for employment of ground and airborne laser systems at the laser range (during both experimental and training activities), and extensive laboratory, ground and flight test activities with state-of-the-art ground/airborne laser systems and laser guided weapons. Between 1997 and 1998 the Italian Air Force Official Flight Test Centre (ItAF-OTC) set the requirements for upgrading the PISQ test/training range (Poligono Interforze del Salto di Quirra - Sardinia - Italy), adding new facilities for carrying out safe training and experimental activities with airborne and ground laser systems, together with LOW delivery tests. According to these initial requirements, the PILASTER (PISQ LASer Test and Evaluation Range) research and development program was divided in two different phases. The aim of the first phase of the program (1999-2002) was to provide an initial operational capability for carrying out, in fully safe conditions, ground tests and flight experimental activities (with related measurements and semi-automated data analysis), required for performance evaluation of military laser systems. The successive phase of the program (still ongoing) is aimed to implementing the PILASTER full operational capability, required for performing all laser test/training activities, including all mission planning and fully-automatedpost-mission data analysistasks (2002-2004). Implementation of suitable mathematical models for laser systems performance analysis (i.e., atmospheric propagation, mission geometry, target back-scattering, etc.) is an essential requirement of the PILASTER program, due to the need for 'realistic' simulation and mission planning, together with reliable post-mission data analysis at the vi range. Very important is also the definition of eye-safety criteria and procedures, since most of current laser systems operate in the near infrared, with considerable risk for the naked human eye. In this research, present laser technology status and future technology trends are investigated, with particular emphasis for the systems now in service or under development for the Italian Air Force. These include the Thompson Convertible Laser Designation Pod (CLDP), The ELOP Portable Laser Designator (PLD) system, Laser Guided Bombs (e.g., PAVEWAY 11, PAVEWAY III and Lizard), and the Marconi- Selenia Laser Obstacle Avoidance System (LOAS) for helicopters. Furthermore, suitable mathematical models for ground/airborne laser systems performance analysis and mission planning are presented, together with innovative methods for evaluating the hazards associated with the use of ground and airborne laser systems at the PILASTER range. Particularly, after describing the technical requirements and design characteristics of the PILASTER range instrumentation, safety issues of state-of-the-art ground/airborne laser systems are thoroughly investigated, in order to identify operational procedures and limitations for the safe employment of such equipment at the PILASTER range during execution of both test and training missions. Furthermore, various mathematical algorithms are presented, developed for the PILASTER simulation and mission planning tools, that allow a complete verification of laser-safety for ground and airborne laser systems. Extensive laboratory, ground and flight experimental activities is performed with both ground and airborne laser systems in order to test the various PILASTER laser range systems and to validate/refine the models developed for systems performance analysis and simulation. Furthermore, the LOAS system is tested both on the ground and in flight, in order to assess the system obstacle detection performance in various weather conditions, and the efficiency of the algorithms developed for obstacle classification and trajectory optimisation.